2010
DOI: 10.1016/j.juro.2010.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Urethral Diverticula in Women: Discrepancies Between Magnetic Resonance Imaging and Surgical Findings

Abstract: In cases clinically suspicious for urethral diverticulum magnetic resonance imaging had a 24.4% error rate. Serious consequences are failure to detect cancer and suboptimal treatment for urethral diverticulum. The reason for the high magnetic resonance imaging accuracy rate in other series may be that in the absence of radiological confirmation some surgeons may choose not to perform surgery. Magnetic resonance imaging is useful to assess urethral diverticula but physicians should be aware of its limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 14 publications
4
24
0
Order By: Relevance
“…When imaging was performed by using high resolution techniques, MRI accuracy improved to 81.8%. The overall accuracy rate in our study is comparable to that of Chung et al [15], who found a 24.4% error rate for MRI when examining for urethral diverticula compared to surgical diagnosis. In these cases, MRI often underdiagnosed diverticula or missed a urethral malignancy [15].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…When imaging was performed by using high resolution techniques, MRI accuracy improved to 81.8%. The overall accuracy rate in our study is comparable to that of Chung et al [15], who found a 24.4% error rate for MRI when examining for urethral diverticula compared to surgical diagnosis. In these cases, MRI often underdiagnosed diverticula or missed a urethral malignancy [15].…”
Section: Discussionsupporting
confidence: 86%
“…The overall accuracy rate in our study is comparable to that of Chung et al [15], who found a 24.4% error rate for MRI when examining for urethral diverticula compared to surgical diagnosis. In these cases, MRI often underdiagnosed diverticula or missed a urethral malignancy [15]. This may be related to mass size fluctuation or lack of fluid distending the diverticulum [15].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, Chung et al reported that in cases of clinically suspicious urethral diverticula, 24.4% of patients showed substantial discrepancy between the operative findings and the results of MRI. In their study, 2 patients had a major discrepancy regarding the site or anatomy of urethral diverticulum, which made intraoperative decision difficult [16]. Furthermore, in a view of ostia, MRI does not provide excellent sensitivity.…”
Section: Discussionmentioning
confidence: 97%